Menelisik Peran Teknologi Blockchain dalam Sistem Informasi Keuangan untuk Mewujudkan Transparansi dan Keamanan Data - Peres Bagan Tua Sihombing; Budianto Bangun; Syaiful Zuhri Harahap (LPPM UNIVERSITAS BINA INSAN, 2026)
This study examines the role of blockchain technology in financial information systems in response to structural weaknesses of conventional systems, particularly data manipulation risks, limited transparency, and information security vulnerabilities. The study aims to develop a conceptual understanding of how blockchain’s technical characteristics contribute to enhancing transparency and data security in financial information systems. A descriptive qualitative approach was employed through a literature review using thematic synthesis, analyzing and synthesizing findings from scientific journals, reference books, and relevant publications from the last five years. The results indicate that blockchain enhances transparency through immutable and traceable distributed ledgers, while strengthening data security through cryptographic mechanisms and network consensus. The conceptual novelty of this study lies in systematically linking blockchain’s technical attributes decentralization, immutability, and consensus to transparency and security dimensions as the foundational structure of financial information systems. The findings propose a conceptual model that can serve as an analytical framework for designing and evaluating blockchain-based financial information systems.